2021
DOI: 10.3389/fpsyt.2021.679451
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Profiling of Late-Pregnant Women With Antenatal Depressive Symptoms

Abstract: Background: Antenatal depression (AD) is a major public health issue worldwide and lacks objective laboratory-based tests to support its diagnosis. Recently, small metabolic molecules have been found to play a vital role in interpreting the pathogenesis of AD. Thus, non-target metabolomics was conducted in serum.Methods: Liquid chromatography—tandem mass spectrometry—based metabolomics platforms were used to conduct serum metabolic profiling of AD and non-antenatal depression (NAD). Orthogonal partial least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It is widely accepted that oral contraceptives could manage menstrual pain by suppressing ovulation and endometrial ) is metabolized in PC synthesis and the glycerophospholipid metabolism pathway, and disturbance of the latter is associated with depression. Recent studies revealed that serum levels of PC (16:0/16) were elevated in antenatal depression and showed a positive trending correlation with depression scores [11][12][13]. Abundant evidence has uncovered psychological risk factors associated with PD, including depression and anxiety, and psychotherapy inter-ventions are considered effective in PD accordingly [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that oral contraceptives could manage menstrual pain by suppressing ovulation and endometrial ) is metabolized in PC synthesis and the glycerophospholipid metabolism pathway, and disturbance of the latter is associated with depression. Recent studies revealed that serum levels of PC (16:0/16) were elevated in antenatal depression and showed a positive trending correlation with depression scores [11][12][13]. Abundant evidence has uncovered psychological risk factors associated with PD, including depression and anxiety, and psychotherapy inter-ventions are considered effective in PD accordingly [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the untargeted metabolomics results showed that the sE2 caused the imbalance of multiple metabolites involved in glycerophospholipid metabolism, retrograde endocannabinoid signaling, and so on, which are associated with depression. Previous studies have shown that gut microbes induce depression by regulating glycerophospholipid metabolism, people with sleep deprivation and depression have abnormal glycerophospholipid metabolism, while abnormal glycerophospholipid metabolism also occurs in the brain of the depression rat model [57][58][59][60]. However, the molecular mechanisms regulating the participation of these metabolites in the above metabolic pathways remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS lipid metabolite profiling in the hippocampus of PSD rats showed 50 key metabolites were reduced, and these were mainly involved in glycerophospholipid metabolism (particularly cardiolipin metabolism) [66]. Glycerophospholipid metabolism was also associated with the pathogenesis of PSD in humans [67,68]. Various lipidomics studies have confirmed that peripheral and central glycerophospholipid metabolism disorders are involved in the pathogenesis of depression via the microbiome-gut-brain axis [69][70][71][72].…”
Section: Lipidsmentioning
confidence: 99%